2D boron nanosheet architectonics: opening new territories by smart functionalization. Issue 6 (26th January 2022) - Han, Chao; Han, Rui; Zhang, Xin; Xu, Zhimei; Li, Weijie; Yamauchi, Yusuke; Huang, Zhenguo
Abstract : The lack of stability hinders the applications of pristine borophene. Functionalization imparts both stability and tunable properties allowing for wide application. This review focuses on the applications of functionalized 2D boron nanosheets. Abstract : Due to its low atomic weight, two-dimensional structure, and unique physical and chemical properties, borophene has attracted strong interest from researchers across different fields. Currently, the experimentally realized polymorphs of single-atomic-layered borophene are all grown on substrates and free-standing forms are yet to be obtained, thus restricting the applications. Functionalizing borophene and boron nanosheets, such as attachment of surface functional groups, heteroatom doping, and formation of composites, not only improves structural stability but also generates new physical and chemical properties. Therefore, functionalized borophene/boron nanosheets with new features have more versatile applications than pristine ones. This review summarizes the recent advances in both theoretical prediction and experimental work of functionalized borophene/boron nanosheets. Various functionalization techniques are systematically reviewed with in-depth discussion of their effects on the properties and performance when utilized in various devices. The advantages and limitations of the functionalization methods are discussed with the aim to stimulate thoughts for future research on boron nanosheets, which are believed to possess a plethora of applications in fields such as electronics, energy, biochemistry, and optics, just to name a few.